1981
DOI: 10.3382/ps.0601043
|View full text |Cite
|
Sign up to set email alerts
|

The Viscosity Interaction of Barley Beta-Glucan with Trichoderma viride Cellulase in the Chick Intestine

Abstract: A culture filtrate from Trichoderma viride was used as a source of cellulose degrading enzymes. This filtrate, when added to a barley ration fed to chicks, improved growth and feed efficiency by 19% and 8%, respectively. The response was saturable since increasing amounts of filtrate above 50 mg/kg produced no further improvement. Barley eta-glucan was added to a corn-based diet (10 g/kg) to evaluate the effect of the culture filtrate on the viscosity of beta-glucan in the chick intestinal contents. Barley bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Enzymes have been extensively used in the past decade as additives to poultry diets (Campbell and Bedford 199b. Numerous studies have demonstrated the benefits of crude enzyme preparations when added to barley-containing diets (Suga et al 1978;Hesselman et al 1981;White et al 1981;Classen et al 1985: Rotter et ai. 1990).…”
mentioning
confidence: 99%
“…Enzymes have been extensively used in the past decade as additives to poultry diets (Campbell and Bedford 199b. Numerous studies have demonstrated the benefits of crude enzyme preparations when added to barley-containing diets (Suga et al 1978;Hesselman et al 1981;White et al 1981;Classen et al 1985: Rotter et ai. 1990).…”
mentioning
confidence: 99%
“…But anti-nutritive factors in barley limit its use in feed industry [1] . The predominant anti-nutritive factor is non-starch polysaccharides (NSP), including β-glucan ((1-3), (1-4)-β-D-glucan) [2,3] and arabinoxylan [4] . The β-glucan and pentosan content in whole barley grain was 4.2% and 6.6%, being 1.8% and 1.4% in endosperm [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The high amount of (1, 3-1, 4)-␤-glucans present in the endosperm walls is the reason why barley is considered a low-metabolic energy feed grain and therefore is an unacceptable component in chicken feed for poultry. The birds do not produce an enzyme in their gastrointestinal tract to depolymerize the (1, 3-1, 4)-␤-glucans, and this leads to a high viscosity of the feed in the intestine, a limited uptake of nutrients, and sticky droppings adhering to the chickens and the floors of the production cages (36,37). Inclusion of fungal enzyme preparations or purified (1, 3-1, 4)-␤-glucanase from Bacillus amyloliquefaciens to barley diets can overcome the nutritional deficiencies of barley grain and prevent the occurrence of sticky droppings (38,39).…”
Section: Discussionmentioning
confidence: 99%